Sikap dan Perilaku Birokrat Garis-Depan dalam Pelayanan Publik Ditinjau dari Perspektif Islam - Hasniati Hasniati (AL-Fikr, 2013)
The spirit of Islam has taught all mankind to always provide a quality service. As God reveals in the Qur'an, in chapter al-Baqarah verse 267, the leading edge bureaucrats should serve and treat people with righteousness and without favoritism, just as if they treat their own selves. Among the substantial aspects required to accomplish better public service and quality is the attitude and behavior of these front-line bureaucrats. In this article, the author refers to the nature of the Prophet Muhammad to serve as an uswatun hasanah (good example) in attitude and behavior when providing services to the public. The Prophet has genuine characters of siddiq, amanah, tabligh, dan fathonah. These four noble qualities have majorly influenced his behavior so as to always perform praiseworthy characters and behavior towards fellow creatures. More specifically especially upon his people, he would serve without any distinctions or discrimination in terms of social status, skin color, ethnicity or class.